Digital banking and banking-as-a-platform - Beeson, Will (Henry Stewart Talks, 2017)
Legacy systems and culture of incumbent banks, Changing business models, PSD2 and Open Banking, Bank-as-a-platform, Unbundling and rebundling of financial services, Neobanks, Future of digital banking